A new dark ice albedo threshold and its applications - Shunan Feng; Christopher J Williamson; Joseph M Cook; Yukihiko Onuma; Nozomu Takeuchi; Alexandre Magno Anesio; Liane G Benning; Martyn Tranter (Environmental Research Letters, 2025)
Dark ice (low albedo) areas are hot spots for investigating biological and abiotic darkening processes and their impact on the melt rate of the Greenland Ice Sheet. This study introduces a quantitative method for determining albedo thresholds to delineate areas of dark ice, which detects abrupt changes in the mean and linear trends in time series of weather station albedo measurements in documented dark ice areas. Four different stages of albedo change during the melt season are easily identified within data derived from program for monitoring of the Greenland Ice Sheet and the Greenland climate network automatic weather station located in dark ice areas. The third stage is defined as the dark ice period, during which the albedo decline rate is lowest, gradually converging to the minimum annual value. The derived broadband albedo thresholds are α  < 0.451 and 0.431 for use with discrete data mapping and linear trend analysis, respectively. We recommend that the latter threshold is used because it can better indicate albedo trend changes. The thresholds were applied to harmonized Landsat and Sentinel 2 ice albedo and MODerate resolution Imaging Spectroradiometer MOD10A1 albedo products to analyze dark ice variations at local (30 m) and regional (500 m) scales on the ice sheet. Our findings reveal notable inter-annual and daily variations in dark ice areas, in line with previous studies. Dark ice occupies, on average, 60% of the bare ice area, and the transition from bare to dark ice averaged 5–6 d across the ice sheet. The impacts of the different thresholds applied are relatively minor.